READING MOTIVATION OF ENGLISH EDUCATION STUDY PROGRAM AT SECOND SEMESTER STUDENTS OF MERANGIN UNIVERSITY - Hartati, Hera; Oktawati, Herysa; Pratiwi, Anggia (INOVISH JOURNAL, 2024)
The  purpose of      this  research  was    to  describe about  students’ motivation  in reading  at  second  semester  of  English Education Study Program in  academic  year  2023/2024. The reading motivation is needed by the students, because it is the reason or a motive why a student starts to reading. While, reading is an activity to get information as source of knowledge for students, it also can support them in doing their task in academic aspect and life in their future. This  reasearch  is  descriptive  quantitave  research. It   conducted  in English Educational  Program  of  Merangin University  . The  population  is  the  second semester students  consists  of  28  students the sample of this reaserach is total sampling. The researcher used Motivation for Reading Questionnaire (MRQ) that filled by students as the instrument of collecting data. The instrument used   four Likert scale, ranging from one to four, with scale of very different from me, a little different from me, a little like me, and a lot like me. In analyzing the data by connecting between the indicators of Motivation for Reading Questionnare  consisted of 53 items, questionnaire is divided into three categories of competence and self-efficacy beliefs, goals for reading, and  social purposes   of   reading.   While   the   dimensions   are     self-efficacy,  challenge,  work avoidance, curiosity, involvement, importance, recognition, grades,   competition,   social, and   compliance. it    classified into high and low reading motivation. Based on calculating the data, the result shown that second semester students of English Education Study Program Merangin University had high reading motivation. It also shown that students had high category in reading compliance and low in work avoidance. The lecturer should use this instrument to know about students reading motivation before start to teach reading subject in the class. Therefore, she or he can design good ways to teach it.